Worker characteristics, job characteristics, and opportunities for phased retirement - Robert M. Hutchens (Institute for the Study of Labor (IZA), 2007)
This paper uses a telephone survey of 950 employers to examine employer-side restrictions on phased retirement. Not only did the survey collect information on establishment level policies, it also asked questions about a specific worker's opportunity for phased retirement. The paper uses these data to first establish that employers are selective when offering opportunities for phased retirement. It then examines what worker and job characteristics are particularly important in the selection process
urn:nbn:de:101:1-20080425327
Keywords: 330; Flexible Altersgrenze; Teilzeitarbeit; Arbeitsplatz; Betriebliche Sozialleistungen; USA